2017
DOI: 10.1136/bmjopen-2016-014399
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of TV viewing and prevalence of overweight and obesity among adult women in Bangladesh: a cross-sectional study

Abstract: BackgroundResearch in developed countries has demonstrated an association of varying degrees between watching TV and the risk of being overweight and obese. However, there is no evidence of such an association in the context of the South Asian population.ObjectiveTo investigate whether watching TV increases the risk of being overweight and obese among women in Bangladesh.SettingRural and urban areas in Bangladesh.ParticipantsParticipants were 16 624 non-pregnant women aged between 15 and 49 years.MethodsThe st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
75
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(109 citation statements)
references
References 29 publications
28
75
0
4
Order By: Relevance
“…3, residing in the Hill region, were educated up to the primary level, and belonged to the richest wealth quintiles. All of these findings are consistent with previous studies conducted in Nepal and in neighboring India and Pakistan [14,38,39]. In general, the prevalence of overweight and obesity was found to be higher among urban women compared to rural women, which is also consistent with findings from earlier studies conducted in Nepal and other South Asian countries [16,36,21].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…3, residing in the Hill region, were educated up to the primary level, and belonged to the richest wealth quintiles. All of these findings are consistent with previous studies conducted in Nepal and in neighboring India and Pakistan [14,38,39]. In general, the prevalence of overweight and obesity was found to be higher among urban women compared to rural women, which is also consistent with findings from earlier studies conducted in Nepal and other South Asian countries [16,36,21].…”
Section: Discussionsupporting
confidence: 92%
“…It was also found that the frequency of watching television at least once a week is higher among urban women compared to rural women. Similar findings were also made in Bangladesh and Myanmar [14,16]. Potential explanations for this phenomenon include a higher and more stable coverage of electricity, as well as the availability of more diverse satellite television channels [15.16].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The mechanism through which urbanicity influences overweight is believed to be linked with dietary and lifestyle factors such as sedentary lifestyle, lower need for strenuous activity, high fat and sugar diet and more take away meals. Urban population also tend to have better access to educational and employment opportunities that are also strongly correlated with economic well‐being and adoption of obesogenic lifestyle habits . As supported by the current findings, women with better education and wealth status are at greater likelihood of being oversized.…”
Section: Discussionsupporting
confidence: 74%
“…Prolonged screen-time leads to passive snacking and drinking of beverages [58]. Highly sedentary behavior, such as watching television, is frequently associated with an increased risk of obesity [59].…”
Section: Discussionmentioning
confidence: 99%